Analisis Nilai Tambah dan Sikap Konsumen Tanaman Herbs menjadi Bubuk Herbs pada CV SOGA Farm Indonesia - Tanjung, Dahri; Fidelia, Indi (Universitas Galuh, 2025)
CV SOGA Farm Indonesia experiences overproduction of vegetables including basil leaves and oregano leaves every month, this is due to fluctuating and erratic supermarket demand. One alternative is to utilize over production into a processed product called herb powder. The purpose of this study is to analyze the financial and non-financial aspects, analyze the amount of added value, and to analyze consumer attitudes towards herb powder. Respondents were selected by accidental sampling method as many as 43 people. The results showed that the magnitude of the value-added ratio was 43% for basil powder while for oregano powder it was 44% this value had a high category. The results of the consumer attitude score of 13 attributes towards powdered herbs, consumers prefer powdered oregano products compared to powdered basil. Therefore, CV SOGA Farm Indonesia can develop herb powder products and can maintain attributes that have superior performance so that consumers still like herb powder products.